Nursing Careers: What Motivated Nurses to Choose their Profession? - McCabe, Rebecca; Nowak, Margaret; Mullen, Scott (National Institute of Labour Studies, 2005)
This paper considers self-reported reasons for choosing to be a nurse and intentions related to remaining in the profession. The data are drawn from a survey of Western Australian Registered Nurses which was part of a broader study of issues for recruitment and retention of nurses in the context of current labour market opportunities for women. The paper finds that what we have termed the 'intrinsic attraction' of nursing has been a key element in the decision to enter nursing for the bulk of nurses, while 'employment security' aspects of the job are also a focus. Interestingly, only a minority of nurses rated the 'extrinsic rewards' highly as a factor in decision making. The paper notes that there are some areas of significant difference in nursing career selection motivation between older and younger nurses; this finding does have policy implications for both health authorities and employers.